Territorial complexity in an urban-rural interface area of Bogotá through structural and strategic content analysis - González Pinto, Alba Luz; Barrera Lobatón, Myriam Susana (Universidad Pedagógica y Tecnológica de Colombia, 2024)
For the “cerros orientales” Adequacy Strip, there is information that requires a multidimensional approach from a complexity perspective. Based on public and open access information in digital media on the web with reference to this area, a content analysis was carried out to identify the associated variables and actors, a structural analysis to establish the influence and dependence relationships of the variables. and a strategic analysis to establish the relationships of convergence and divergence between actors. The above showed that the key variables for its operation correspond to the management of public administration, territorial planning, judicial management and response, and environmental conservation, which are strongly influenced by risk management and are complemented by the management and legislative response. As for the actors, the judicial bodies exert the greatest influence on the construction companies and owners, possessors or holders, with whom greater integration should be sought, while, for the Mayor's Office of Bogotá, the environmental authorities and the communities and inhabitants, It is important to continue strengthening agreements that maximize the expected results.